Improving gender equity in irrigation: application of a tool to promote learning and performance in Malawi and Uzbekistan - Lefore, Nicole; Weight, Elizabeth; Mukhamedova, Nozilakhon (International Water Management Institute, 2017)
This paper provides a brief synthesis of research conducted on gender in irrigation, and the tools and frameworks used in the past to promote improvement for women in on-farm agricultural water management. It then presents results from the pilot of the Gender in Irrigation Learning and Improvement Tool (GILIT) in locations in Malawi and Uzbekistan in 2015. Through the results of the tool, the paper looks at benefit sharing between men and women farmers: (i) access to irrigation scheme resources (including information, for example, in the design phase; land, water and other inputs); (ii) participation in scheme management; and (iii) access to scheme benefits, including access to market information, packaging and payments. The indicators for the tool were modelled after principles reflected in existing gender policies and strategies, and intended to improve performance at field level in line with national and regional goals. The paper concludes with informal and formal constraints to gender-equitable outcomes from irrigation investments identified during the pilot, and suggests how the tool can be used by various development actors to improve the benefits for women from investments in agricultural water management.